Climate Change and the Nervous System - Sharma, Mohan Raj; Pyakurel, Manita (Nepal Journal of Neuroscience, 2024)
Climate change has received significant media attention. The recent COP 28 summit in November and December 2023 in Dubai has once again brought together the leaders of all countries and has made everyone aware of its effect on global health. Despite this attention, scholarly works on the subject, particularly from developing economies are relatively scarce.